Novel Strategies for the Development of Healthier Meat and Meat Products and Determination of Their Quality Characteristics - Ruiz-Capillas, Claudia; Herranz, Ana Herrero (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Meat and meat products are in demand worldwide. However, new trends and innovations, driven by consumer interests and demands, have contributed to the development of healthier meat products, which are growing exponentially. Health is one of the main criteria for consumers when choosing the type of food they eat. This, along with more sustainable global production, changes in lifestyles, and nutritional ideologies among the population, has led to a growing demand in the market for healthier and more functional foods. This Special Issue has collected nine original research articles and one editorial. This book collects all-new, relevant information on the different strategies for modifying meat and meat products to make them healthier and more sustainable and the different quality control methods for their control. With this information, we hope to shed more light on this important topic. This SI will prove very useful and interesting to all those involved in the meat and meat product industry (livestock producers, processing companies, researchers, scientists, consumers, administration, etc.). Lastly, many of the studies featured in this SI leave the door open to future research in this area of growing interest, not only for the meat and meat product industry but for other foods as well.